PENGARUH PENDEKATAN MINDFUL LEARNING TERHADAP HASIL BELAJAR IPAS KELAS V SEKOLAH DASAR - Abdurrochim, Putri Laisya; Hanifah, Nurdinah; Syahid, Aah Ahmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Elementary schools' IPAS (Natural and Social Sciences) learning process still emphasizes transforming factual information and developing verbalistic reasoning. Also, the presentation process has yet to be integrated, as science and social studies are still taught separately, and its evaluation process is still based on students' comprehension of a concept. This study aims to analyze the effect of a mindful learning approach on science and social studies (IPAS) learning outcomes in the fifth-grade elementary school class focusing on the topic